2012
DOI: 10.1007/s00595-012-0192-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant sternal metastasis secondary to follicular carcinoma of the thyroid gland: report of a case

Abstract: A 70-year-old woman was admitted to our department for investigation and treatment of a progressively enlarging multinodular goiter and a fast growing mass infiltrating the sternum. The patient was euthyroid, but computed tomography (CT) and ultrasonography showed a mass in the anterior mediastinum infiltrating the sternum, with a dominant nodule in the right lobe of the thyroid. Fine needle aspiration biopsy results from both the cervical and the mediastinal masses were suggestive of follicular thyroid carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Marginal vacuoles are variable sized and show slight eosinophilic discolouration at the periphery of the vacuoles. Similar cytological features have been observed by some other authors also …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Marginal vacuoles are variable sized and show slight eosinophilic discolouration at the periphery of the vacuoles. Similar cytological features have been observed by some other authors also …”
Section: Discussionsupporting
confidence: 91%
“…Tissue diagnosis, either by biopsy or fine needle aspiration, is necessary to confirm or refute the diagnosis of metastatic disease. Although distant metastases from follicular carcinoma have been reported in literature, only a few reports illustrating their cytomorphologic features are available …”
mentioning
confidence: 99%
“…Autoplastic reconstruction is indicated for smaller defects, while alloplastic materials are indicated for larger defects. Several studies have reported good results in response to reconstruction with skin flap, myocutaneous flaps, Marlex mesh, Gore-Tex dual mesh, methyl methacrylate sandwiched between Marlex mesh, steel mesh to titanium plate, and so on [1, 6, 7]. In the present case, reconstruction was performed with a polypropylene/ePTFE composite, which is originally used for the reconstruction of the abdominal wall [8].…”
Section: Discussionmentioning
confidence: 97%
“…Bone and soft tissue reconstruction should be considered separately. Multiple methods of reconstruction of the sternum have been described including methyl methacrylate and synthetic mesh [8][9][10]. Our preference ordinarily would be to reconstruct the neo-manubrium with a vascularised bone flap (e.g., free fibula) to provide stability and vascularity.…”
Section: Discussionmentioning
confidence: 99%